2002
DOI: 10.1597/1545-1569(2002)039<0312:iasoos>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Severity of Obstructive Sleep Apnea Following Pharyngeal Flap Surgery in Patients With Cleft Palate

Abstract: Six months following pharyngeal flap surgery, more than 90% of the patients with cleft palate still had OSA. The severity of OSA associated with pharyngeal flap surgery tended to be greater in children than in adults. The flap width was unrelated to the incidence and severity of OSA, no matter in adults or in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 18 publications
1
51
2
1
Order By: Relevance
“…One of the few studies comparing the outcomes of these two surgeries on speech (10) demonstrated that pharyngeal flap was more efficient than intravelar veloplasty for reduction of hypernasality and adequacy of velopharyngeal closure in individuals with residual VPI. Conversely, pharyngeal flap changes the anatomy of the velopharyngeal region and thus alters the permeability of the nasopharynx, possibly leading to undesirable respiratory symptoms as oral respiration, snoring, obstructive sleep respiratory disorders, and even hyponasality (9,15,23,26,27) . In all these studies, surgeries were performed as the single procedure for correction of VPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the few studies comparing the outcomes of these two surgeries on speech (10) demonstrated that pharyngeal flap was more efficient than intravelar veloplasty for reduction of hypernasality and adequacy of velopharyngeal closure in individuals with residual VPI. Conversely, pharyngeal flap changes the anatomy of the velopharyngeal region and thus alters the permeability of the nasopharynx, possibly leading to undesirable respiratory symptoms as oral respiration, snoring, obstructive sleep respiratory disorders, and even hyponasality (9,15,23,26,27) . In all these studies, surgeries were performed as the single procedure for correction of VPI.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus in the literature about the high success rate of pharyngeal flap surgery to reduce or eliminate the speech symptoms caused by VPI (12,13,14) . However, there is concern among clinicians and investigators in this field about surgeries that change the anatomy of the velopharyngeal region and alter the nasopharyngeal permeability, such as the pharyngeal flap (9,13,15) . For this reason, the literature has advocated surgical techniques that allow adequate velopharyngeal closure in a condition more similar to the normal anatomical conditions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the occurrence of respiratory changes after pharyngoplasty is extremely diverse, ranging from 4% to 92% (12)(13)(14) . Such diversity may be related to the methodology used, the age of the population studied and the criteria used to define the presence of respiratory changes, taking into account each patient's individual tolerance of symptoms after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the great success of pharyngeal flap surgery in reducing or eliminating VPI symptoms in speech, with success rates varying between 25% and 98% (8)(9)(10) . However, the pharyngeal flap is also associated with upper airway impairment, which may cause hyponasality, chronic nasal obstruction, snoring and obstructive sleep apnea, symptoms that interfere with respiratory function and, consequently, quality of life (11)(12)(13)(14) . It is also important to consider that a cleft lip/palate determines nasal deformities that often reduce the dimensions of the nasal cavity (15) and increase nasal resistance to respiratory airflow.…”
Section: Introductionmentioning
confidence: 99%
“…Muitos estudos relataram a efetividade do retalho farín-geo na redução dos sintomas da fala (4,6,(10)(11)(12)(13)(14)(15)(16)(17)(18) . Por outro lado, o retalho faríngeo está associado a um potencial e significante de comprometimento das vias aéreas superiores, incluindo-se entre esses comprometimentos desde a hiponasalidade, obstrução nasal crônica, até ronco e apnéia obstrutiva do sono, que podem trazer consequências graves aos pacientes (4,10,(19)(20)(21) . O efeito do retalho faríngeo sobre a fala e a respiração dos pacientes tem sido estudado há anos, no Laboratório de Fisiologia do Hospital de Reabilitação de Anomalias Craniofaciais (HRAC-USP).…”
Section: Introductionunclassified